Analisis Faktor Individualism, Perceived Familiarity, dan Perceived Social Value Terhadap Startup Intentions pada Mahasiswa - Mohamad Fatkhur Rozi; Yusi Tyroni Mursityo; Intan Sartika Eris Maghfiroh (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The development of startup-type businesses in Indonesia is currently quite fast, especially since 2018. This type of startup business has begun to grow along with technological advances that have also triggered disruptive technology in the business sector. Currently, we meet many new businesses that utilize technology which is now known as e-business. Like any business in general, there are factors that affect the running of the business or even affect someone entering the business sector. The purpose of this research is to analyzing factors that influence a person's interest in establishing a startup business. The scope of this research includes 200 Brawijaya University students as respondents in data collection, where based on this data will be investigated the influence of Individualism, Perceived Familiarity, and Perceived Social Value factors on Startup Intentions in students. In this study, online questionnaire was used as a data collection instrument, then the PLS-SEM was used as a data analyzing method that had been obtained. Based on this analysis, it is known that majority respondents agree with the statements submitted through the questionnaire, because the average results obtained on a scale of 4 out of 5 for each statement. Furthermore, based on the hypothesis test results, it is known that each of the individualism, perceived familiarity, and perceived social value factors has a significant and positive influence both partially and simultaneously on student startup intentions.